Activate Creative Islamic Education : Inspiration for Innovation in the Automotive World - Mubin, Nurul; El Syam, Robingun Suyud (UNIVERSITAS PAKUAN, 2023)
The purpose of this article is to propose the activation of Islamic creative education through inspiration from innovations in the automotive world, by emphasizing that creativity will emerge in the spirit of taking inspiration from innovations in other fields. This article is a library research that explores relevant data from books, literature, documents, journals, articles, and other information. Data is collected, selected, and grouped for discussion and analysis using content analysis in an in-depth study. Research concludes: Creative education is based on the premise that creativity must be a key element in the education system. The creativity of Islamic education can refer to moderating the mediating effect of innovation in the automotive world. Creative Islamic education is highly dependent on a conducive teacher-student relationship and is driven by the role of a creative teacher. So Islamic education teachers must continue to learn from existing innovations so that creativity continues to be honed.